2015
DOI: 10.1155/2015/597475
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Thresholding Technique for Retinal Vessel Segmentation Based on GLCM-Energy Information

Abstract: Although retinal vessel segmentation has been extensively researched, a robust and time efficient segmentation method is highly needed. This paper presents a local adaptive thresholding technique based on gray level cooccurrence matrix- (GLCM-) energy information for retinal vessel segmentation. Different thresholds were computed using GLCM-energy information. An experimental evaluation on DRIVE database using the grayscale intensity and Green Channel of the retinal image demonstrates the high performance of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(28 citation statements)
references
References 36 publications
0
28
0
Order By: Relevance
“…Fully connected conditional random field model efficiently extract the thin and elongated structure of retinal vessels structure [16]. Mapayi et al [17], presented Gray Level Cooccurrence Matrix (GLCM) based on adaptive thresholding to extract retinal vessel tree. Zhao et al [18], suggested a graph cut approach for segmentation of retinal vasculature.…”
Section: Review Of Segmentation Methodsmentioning
confidence: 99%
“…Fully connected conditional random field model efficiently extract the thin and elongated structure of retinal vessels structure [16]. Mapayi et al [17], presented Gray Level Cooccurrence Matrix (GLCM) based on adaptive thresholding to extract retinal vessel tree. Zhao et al [18], suggested a graph cut approach for segmentation of retinal vasculature.…”
Section: Review Of Segmentation Methodsmentioning
confidence: 99%
“…In [21], Odstrcilik et al presented a method that extract the blood vessel using kittler minimum error thresholding method. In [22], Mapayi et al proposed a local adaptive thresholding method using gray level co-occurrence matrix-energy information to segment retinal blood vessels. In [23], Panda et al used a novel binary Hausdorff symmetry measure based seeded region growing technique to segment retinal blood vessels.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous approaches of adaptive thresholding segmentation based for retinal image analysis have been proposed for the detection of BV, OD, and red lesions [20–25]. BV, both large and thin, in retinal images are unable to segment accurately within a global threshold value . Therefore, local thresholding is required.…”
Section: Introductionmentioning
confidence: 99%